2015
DOI: 10.1108/jkm-10-2014-0435
|View full text |Cite
|
Sign up to set email alerts
|

Resolving authorization conflicts by ontology views for controlled access to a digital library

Abstract: Purpose – This paper provides a new Digital Library architecture that supports polyhierarchic ontology structure where a child concept representing an interdisciplinary subject area can have multiple parent concepts. The paper further proposes an access control mechanism for controlled access to different concepts by different users depending on the authorizations available to each such user. The proposed model thus provides a better knowledge representation and faster searching possibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Skilled human resources and financial resources should be available for the efficient functioning of the integrated semantic digital library system. These findings are in consonance with the research results conducted by Mayr et al (2008), Burke (2009), He et al (2010), Lee (2011), Kao and Wu (2012), Morato et al (2013), Pattuelli and Miller (2015), Dasgupta et al (2015), Solomou and Koutsomitropoulos (2015), Yan et al (2016), Cole et al (2017), Gul and Bano (2019), Warraich and Rorissa (2020), Ali et al (2021), Mehta (2021), Su (2021.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Skilled human resources and financial resources should be available for the efficient functioning of the integrated semantic digital library system. These findings are in consonance with the research results conducted by Mayr et al (2008), Burke (2009), He et al (2010), Lee (2011), Kao and Wu (2012), Morato et al (2013), Pattuelli and Miller (2015), Dasgupta et al (2015), Solomou and Koutsomitropoulos (2015), Yan et al (2016), Cole et al (2017), Gul and Bano (2019), Warraich and Rorissa (2020), Ali et al (2021), Mehta (2021), Su (2021.…”
Section: Discussionsupporting
confidence: 91%
“…SDLs provided controlled access to clients according to their credentials (Dasgupta et al. , 2015); information access tools are provided to the end-users (Mehta, 2021); documents are preserved efficiently (Lee, 2011); the interaction is done with a larger set of users (Morato et al.…”
Section: Results Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Cunningham et al (2005) provide a high-level introduction to IE and descriptions of application scenarios for KM tools that exploit IE. Dasgupta et al (2015) Their co-word occurrence analysis for mapping KM research topics showed that the structure of fundamental subject areas within the KM field has changed and expanded dynamically in 2004-2010. However, they use a single source to construct the corpus, as opposed to various source types (news, Web, blogs and discussion group sites) used in the current research.…”
Section: Literature Reviewmentioning
confidence: 99%